Social and Political Issues on Sustainable Development in the Post Covid-19 Crisis : Proceedings of the International Conference on Social and Political Issues on Sustainable Development in the Post Covid-19 Crisis (ICHSOS 2021), Malang, Indonesia, 18-19 June 2021 - Oman Sukmana; Salahudin; Iqbal Robbie; Ali Roziqin; Shannaz Mutiara Deniar; Iradhad T. Sihidi; Dedik F. Suhermanto (Routledge, 2022)
As a threat, a pandemic has indirect implications for social, economic and political conditions both at domestic and international levels. Thus, collective and comprehensive efforts are needed in responding to and preventing the expansion of infections caused by the virus, including Covid-19. This international conference provides the discourse on social, economic as well as political issues regarding the condition after the pandemic. Social issues are studied through social welfare, sociology, governance, communication and international relations approaches. Meanwhile, economic problems are discussed through business, economic development and economic management approaches. Under the First International Conference on Humanities and Social Sciences (ICHSOS) 2021, speakers from several countries provided solutions and alternative perspectives in preventing and dealing with problems after the Covid-19 pandemic. This book contains 42 papers presented at the conference.